RESTORATION OF MICROBIOCENOSIS OF THE INTESTINES WITHIN THE COMPLEX THERAPY FOR ATOPIC DERMATITIS IN CHILDREN - I.Yu. Mel'nikova; M.M. Goryunova; M.V. Samsonova ("Paediatrician" Publishers LLC, 2007)
Atopic dermatitis is a wide spread disease in the practices of the pediatrician. Quite often, the development of atopic dermatitis among children is accompanied by dysbacteriosis of the intestines, whose correction assisted by the probiotics is not always efficient. The purpose of the present research was to study the «Primadophilus for children» dietary supplement efficacy and safety to restore microbiocenosis of the intestines among children with atopic dermatitis. 102 patients aged between 6 months and 6 years took a part in the open research. It was discovered that most children, who received the dietary supplement along with the basic therapy, showed restoration of the normal intestinal microflora. The positive dynamics of the skin process evaluated according to SCORAD scale was marked among 76% of children from the main group and among 68% of children from the screening group. The most drastic reduction of the SCORAD index (by 16-20 points) was noted among 52% of children from the main group and only among 30% of children from the screening group (p < 0,05). No side effects were reported during the treatment. Thus, the researchers proved that «Primadophilus for children» was an efficient and safe means for the complex therapy for atopic dermatitis among children. Key words: microbiocenosis of the intestines, probiotics, atopic dermatitis, children.